Perfil clínico e epidemiológico de pacientes submetidos a cirurgia bariátrica de um hospital terciário do estado do Ceará - Peter, Claudia Melo (2023)
Introduction: Bariatric surgery is considered the most effective treatment for moderate to severe obesity. The Dr. César Cals General Hospital performs bariatric surgery through SUS (the Brazilian Unified Health System) in Ceará. However, there were no available patient profile data in this hospital. Objective: To characterize the clinical, epidemiological, comorbidity, and weight regain profile of individuals who underwent bariatric surgery. Materials and Methods: This was a cross-sectional observational study on post-bariatric surgery patients using sleeve and bypass techniques for more than 5 years. Data were collected from medical records during the project period from 2019 to 2021. Patients were evaluated for weight regain and control of comorbidities—diabetes mellitus, hypertension, and dyslipidemia—at four time points using the techniques offered at the reference service: pre-surgery, nadir, 24 months, and 60 months post-surgery. Results: Fifty-seven individuals participated, with 43 undergoing Bypass and 14 undergoing Sleeve. In the preoperative period, the mean BMI was 50.3 ± 7.9 kg/m², and the mean age was 40 ± 10 years. The onset of obesity was observed in 30% during adulthood and 28% during childhood. Regarding social stigma, 49% reported experiencing some degree of prejudice due to their obesity condition. Thirty percent were active, and 42% were sedentary. Alcohol consumption was reported by 25% of the sample pre-surgery. Binge eating was reported by 75% pre-surgery. At 60 months, weight regain was observed: 19% for Sleeve and 14% for Bypass. For hypertension (HTN), 89% achieved remission at 60 months, with only 21% remaining hypertensive. For diabetes (DM), 100% achieved remission, with an 18% recurrence rate. In cases of dyslipidemia, remission was 67%, with a 58% recurrence rate after 60 months. Both surgical procedures were successful in controlling comorbidities. Conclusion: Our population consisted of superobese women of productive age. A high percentage of comorbidity reduction was observed with the performed procedures. Weight loss and control of comorbidities did not show differences between the techniques within the 2-year period post-surgery; however, at 60 months, Bypass demonstrated greater control of comorbidities.